Program Edukasi Pemakaian Masker pada Anak Usia Sekolah di Era New Normal - Antikasari, Novika Intan; Mulyanti, Sri; Setyorini, Yuyun (Poltekkes Kemenkes Surakarta, 2023)
Background: School-aged children's knowledge of the correct way to wear masks is still low during the new normal era, which increases the risk of COVID-19 spread in the school environment. Objective: To improve school-aged children's understanding and skills in using masks through community service activities. Methods: The service activity was conducted using a method of counselling and practice at SD Negeri 4 Ngunut, Bandar, Pacitan. The number of partners is 34 students from grades 3, 4, and 5, who were randomly selected. Evaluation was conducted using pre-tests and post-tests with questionnaires that had been tested for validity and reliability, as well as behavioural observation of mask usage. Results: There was an 86.5% increase in participants' knowledge, as evidenced by an increase in the average score from 1.09 (pre-test) to 2.03 (post-test). This increase indicates a significant behavioural change in the correct use of masks, potentially reducing the risk of disease transmission. Conclusion: This community service successfully improved soft skills such as understanding health protocols and hard skills in the correct use of masks among school children. This interactive service program needs to be continued and developed to maintain the sustainability of health protocol adaptation in the educational environment.